1996
DOI: 10.1089/aid.1996.12.1237
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Human Immunodeficiency Virus Replication in Differentiating Monocytes by Interleukin 10 Occurs in Parallel with Inhibition of Cellular RNA Expression

Abstract: The mechanism of inhibition of HIVBa-L replication by interleukin 10 (IL-10) in primary monocytes and macrophages at various stages of maturation was investigated using semiquantitative PCR for reverse-transcribed HIV DNA, and Northern hybridization for HIV mRNA expression in comparison with extracellular p24 antigen. Pretreatment of monocytes with IL-10 markedly inhibited expression of both unspliced and spliced HIV RNA, reaching a nadir at 7 days and recovering to normal levels by 10 days after a single appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…IL-10 and TNF- have been shown to have different effects on HIV replication in macrophages depending on the experimental conditions. Indeed, treatment of primary macrophages with IL-10 abrogates HIV-1 infection by inhibiting the production of both spliced and unspliced HIV-1 RNA transcripts and by interfering with protein processing Naif et al, 1996). However, another study found that IL-10 promotes the productive infection of monocytes by the R5 virus by selectively upregulating CCR5 and increasing viral entry (Sozzani et al, 1998).…”
Section: Macrophage Antiviral Factor "Maf"mentioning
confidence: 99%
“…IL-10 and TNF- have been shown to have different effects on HIV replication in macrophages depending on the experimental conditions. Indeed, treatment of primary macrophages with IL-10 abrogates HIV-1 infection by inhibiting the production of both spliced and unspliced HIV-1 RNA transcripts and by interfering with protein processing Naif et al, 1996). However, another study found that IL-10 promotes the productive infection of monocytes by the R5 virus by selectively upregulating CCR5 and increasing viral entry (Sozzani et al, 1998).…”
Section: Macrophage Antiviral Factor "Maf"mentioning
confidence: 99%
“…MDMs were cultured from the peripheral blood of healthy HIV-seronegative donors and infected with the laboratory-adapted M-tropic strain HIV-1 BaL (multiplicity of infection [MOI], 0.02) as described previously (10). In the first set of experiments, cells from four donors were exposed to the test compounds at 0, 1, and 10 M over 28 days.…”
mentioning
confidence: 99%
“…COX-2 and PGE 2 also inhibit programmed cell death and facilitate tumor formation (33,34), and thus these activities might promote lymphosarcoma and leukemia with other carcinogenic factors, such as Bcl-2 and BLV Tax protein, in BLV infection. Thus, in other retrovirus infections, the inhibitory function of IL-10 on human immunodeficiency virus expression has been reported (24,30,31). Most studies have utilized macrophage cell lines and primary macrophages, while the studies with T-cell lines or primary T cells failed to demonstrate the IL-10 inhibition of human immunodeficiency virus expression.…”
mentioning
confidence: 99%